Redesigning systems of school accountability: A multiple measures approach to accountability and support - Bae, Soung (Education Policy Analysis Archives, 2018)
The challenges facing our children in the 21st century are rapidly changing. As a result, schools bear a greater responsibility to prepare students for college, career, and life and must be held accountable for more than just testing and reporting on a narrow set of outcomes aimed at minimum levels of competency. Thus, scholars, educators, and reform advocates are calling for a more meaningful next phase of school accountability, one that promotes continuous support and improvement rather than mere compliance and efforts to avoid punishment (Center for American Progress & CCSSO, 2014; Darling-Hammond, Wilhoit, & Pittenger, 2014). This paper reviews state and district level accountability systems that incorporate a multiple measures approach to accountability and highlights the following features that represent redesigned systems of accountability: 1) broader set of outcome measures, 2) mix of state and local indicators, 3) measures of opportunities to learn, 4) data dashboards, and 5) School Quality Reviews. The paper concludes with guidance for policymakers and practitioners on ways to support the development and implementation of a multiple measures system of accountability so that school accountability becomes synonymous with responsibility for deeper learning and support for continuous improvement.